(untitled) (Jurnal Manajemen Bisnis, 2024)
One of the most important aspects of employee engagement is the focus on managing new organizational dynamics. The purpose of this study is to analyze narratively and simultaneously the influence of employee leadership and organizational commitment on employee performance at PT Bank Rakyat Indonesia. The method used is quantitative and survey methods, data collection is done through questionnaires. The respondents of this study are a combined sample that includes all permanent employees. A total of 38 people used single regression and multiple regression methods in data analysis to test the relationship and influence of independent variables on dependent variables. The findings show that employee leadership and one-time management commitment have a significant impact on improving employee performance. However, the noble side of a servant has signs that are not included in the category of goodness, namely the romantic side. Management hopes that this can encourage managers to give praise regularly, not only for big achievements but also for small things that support improving employee performance.